Measurement opportunities of labour market requirements of university students - Kollár, Péter (Studia Mundi – Economica, 2019)
Competency-based education, as a representative concept addressing the educational and employee development challenges, encompasses multiple theoretical and pragmatic approaches with various scopes of analyses. In this research, the reader is tried to introduce to a data-driven[1]or big-data-based method. The goals of this research are to investigate how behaviour patterns related competencies can be identified and measured using the strength of log file and records, and to develop a professional system that is able to foresee training needs based on similarity analyses enabling artificial intelligence-based term-creation processes.